Critical Approach to (Un)justified Overcriminalization in the Economic Field - Kostic, Jelena Ž. (NBP. Nauka, bezbednosti, policija, 2023)
In recent years, the spread of incriminactions in the economic field has been very present. One of the reasons for this is the harmonization of national legislation with acquis communautaire. Bearing in mind the views of other authors, in this paper we started from the assumptions that a large number of economic crimes are unnecessary, because their legal description could be subsumed under already existing crimes, that excessive criminalization can contribute to problems in practice and that procedural legislation often don’t follow the changes in substantive criminal legislation when they are carried out by non-criminal laws, as well as when changing and reforming criminal legislation, crimes prescribed by secondary criminal legislation are generally ignored. Starting from the mentioned assumptions, we try to make recommendations for the further direction of the development of substantive criminal legislation, which, in our opinion, should follow the narrowing of criminal law interventionism in the economic area. The subject of this paper is the analysis of the provisions of secondary criminal legislation, which precisely contain the shortcomings pointed out by the authors when analyzing the need to reform substantive criminal legislation. Therefore, in this paper the dogmatic-legal method is dominant, and special attention is paid to the analysis of the provisions of the Law on Tax Procedure and Tax Administration and the Law on the Capital Market.